2020
DOI: 10.3390/jcm9040986
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions and Emotion Regulation in Attention-Deficit/Hyperactivity Disorder and Borderline Intellectual Disability

Abstract: The main objective of this study is to investigate the multiple relations and to determine the differences between executive functions (EFs), emotion regulation, and behavioral and emotional problems in children with attention-deficit/hyperactivity disorder (ADHD), borderline intellectual disability (ID), and typical development (TD). The sample included 85 children aged 6 to 11 years, 42 with typical development (TD), 27 with ADHD, and 16 with borderline ID. The results emphasized a positive correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…In primary school age, children with BIF are burdened with difficulties in school achievements due to learning difficulties in more than one executive functions domain, such as attention, concentration, planning, and inhibition of impulsive responses, as well as memory and motor skill limitations ( Alloway, 2010 ; Vuijk et al, 2010 ; Salvador-Carulla et al, 2013 ; Peltopuro et al, 2014 ; Contena and Taddei, 2017 ). Furthermore, limitations in social skills, emotional competencies, and behavioral problems affect the social participation of these children ( Baglio et al, 2016 ; Predescu et al, 2020 ). Children with BIF are thus at high risk of school failure and dropout ( Fernell and Ek, 2010 ), and are more likely to develop psychiatric problems in adulthood ( Douma et al, 2007 ; Emerson et al, 2010 ; Gigi et al, 2014 ; Hassiotis, 2015 ; Hassiotis et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In primary school age, children with BIF are burdened with difficulties in school achievements due to learning difficulties in more than one executive functions domain, such as attention, concentration, planning, and inhibition of impulsive responses, as well as memory and motor skill limitations ( Alloway, 2010 ; Vuijk et al, 2010 ; Salvador-Carulla et al, 2013 ; Peltopuro et al, 2014 ; Contena and Taddei, 2017 ). Furthermore, limitations in social skills, emotional competencies, and behavioral problems affect the social participation of these children ( Baglio et al, 2016 ; Predescu et al, 2020 ). Children with BIF are thus at high risk of school failure and dropout ( Fernell and Ek, 2010 ), and are more likely to develop psychiatric problems in adulthood ( Douma et al, 2007 ; Emerson et al, 2010 ; Gigi et al, 2014 ; Hassiotis, 2015 ; Hassiotis et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A high-risk population to be exposed to ACE are children with borderline intellectual functioning (BIF), a condition in between typical development and intellectual disability (Hassiotis et al, 2019 ), characterized by heterogeneous profile including an intelligence quotient (IQ) within the range of 70–85, associated with difficulties in social participation and adaptability. The difficulties in cognitive and social functioning, specifically in executive functioning, language, learning, movement, emotion regulation, coping, and mentalization (Salvador-Carulla et al, 2013 ; Peltopuro et al, 2014 ; Hassiotis, 2015 ; Baglio et al, 2016 ; Contena and Taddei, 2017 ; Alesi et al, 2018 ; Predescu et al, 2020 ) expose individuals with BIF to the risk of developing mental illnesses lifelong (Hassiotis et al, 2019 ). Given these premises, it is crucial to find effective rehabilitation approaches for this population.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been indicated that children with ADHD show more negative affect, greater emotional reactivation and less empathy than children with neurotypical development, and deficits in emotional self-regulation, which increase the risk of functional decline in daily life and comorbidity in these children [3]. ADHD has mainly been explained as a disorder of neurodevelopment of the prefrontal lobe, which affects the development of executive functions in childhood, including inhibitory control, working memory, cognitive flexibility, planning, the performance of goal-oriented behaviors and behavioral self-control [12][13][14]. Recent studies show that deficits in executive functioning and emotional regulation are interconnected, especially since inhibitory control, reasoning, planning and problem solving are prerequisites for emotional regulation [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…ADHD has mainly been explained as a disorder of neurodevelopment of the prefrontal lobe, which affects the development of executive functions in childhood, including inhibitory control, working memory, cognitive flexibility, planning, the performance of goal-oriented behaviors and behavioral self-control [12][13][14]. Recent studies show that deficits in executive functioning and emotional regulation are interconnected, especially since inhibitory control, reasoning, planning and problem solving are prerequisites for emotional regulation [14,15]. Some authors have indicated that cognitive processes underlying executive functions could be understood as "cold" executive functions, while those involved in emotional regulation could be considered "hot" executive functions [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation